Review: Smart city Barcelona: The Catalan quest to improve future urban living - Calzada, I (Intellect Books, 2020)
This is a book review of 'Smart City Barcelona: The Catalan Quest to Improve Future Urban Living'. Published in International Journal of Iberian Studies